2014
DOI: 10.1364/ome.4.001708
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured waveguides in z-cut LiNbO_3 by high-repetition rate direct femtosecond laser inscription

Abstract: Abstract:We report on the operational parameters that are required to fabricate buried, microstructured waveguides in a z-cut lithium niobate crystal by the method of direct femtosecond laser inscription using a highrepetition-rate, chirped-pulse oscillator system. Refractive index contrasts as high as −0.0127 have been achieved for individual modification tracks. The results pave the way for developing microstructured WGs with low-loss operation across a wide spectral range, extending into the mid-infrared re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…The immersion oil layer (RI = 1.523) between the lenses and the sample was checked regularly during the experiment to prevent any formation of air-bubbles or dust that could affect the inscription results. A detailed description of our laser inscription system can be found in Dubov et al 25 . Figure 1b shows an example of a waveguide cross-section, where the circle array represents the track positions programmed into the translational stage controller and the inset shows the actual track positions and shapes after fabrication.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The immersion oil layer (RI = 1.523) between the lenses and the sample was checked regularly during the experiment to prevent any formation of air-bubbles or dust that could affect the inscription results. A detailed description of our laser inscription system can be found in Dubov et al 25 . Figure 1b shows an example of a waveguide cross-section, where the circle array represents the track positions programmed into the translational stage controller and the inset shows the actual track positions and shapes after fabrication.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…In this work, a fixed energy increase rate (∆Ed) of approximately 0.3 nJ (corresponding to 3-mW optical power) per distance between two consecutive track rows was chosen after investigating some try-out fabrications. While the induced RI change of a track increases linearly with the inscribing pulse energy 25 , which is crucial for obtaining strongly confining depressed-cladding waveguides, increased pulse energy is liable to induce structural defects and micro-crack generations along the track. These high-laser-energy driven non-uniformities would result in a reduction of the waveguide performance due to effects such as scattering, absorption, and so on.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…Прямая фемтосекундная запись является перспективной безмасочной и ши-роко распространенной технологией создания оптических волноводов в объеме стекол и кри-сталлов [1][2][3][4][5][6][7]. Оптические стекла и кристаллы могут быть разделены на три группы на осно-ве знака постоянно изменяющегося показателя преломления (ПП): 1) материалы, ПП которых увеличивается при фемтосекундной микрообработке; 2) материалы, ПП которых понижается;…”
Section: ключевые слова: лазерно-индуцированное воздействие фемтосекunclassified
“…This is especially advantageous to the fabrication of complex structures and large-scale commercial production. It is also noteworthy that the energy efficiency of HRR systems can be twice as large as that of LRR systems owing to the heat accumulation effect [18]. Recently, Bhardwaj et al demonstrated depressed-cladding waveguides based on the usual circular packing geometry in a x-cut LN crystal with impressively low losses of 0.56 dB/cm and 0.51 dB/cm for TE (perpendicular to optical axis) and TM (parallel to optical axis) polarized light, respectively, at 1550 nm [17].…”
Section: Introductionmentioning
confidence: 99%